Assessment of Prescribing and Dispensing Practices Based on WHO Core Prescribing Indicators in Hospital and Community Pharmacies in Khartoum State - Sudan - Rabie, Dalia; I. Kheder, Salah (Journal of Medical Informatics and Decision Making, 2020)
Background Rational drug management has become an increasingly important topic in order to make optimal use of the drug budget to offer health services of the highest possible standard. It is important that continuous assessment for rational prescribing and use of drug have to be carried. Objective of this study was to gather data on existing drug prescription and dispensing practices and to evaluate the prescribing and dispensing indicators as described by the WHO. Method Observational, cross-sectional, prospective study was designed and conducted to evaluate the performance of hospital and community pharmacies in Khartoum state, related to rational drug use and prescribing and dispensing practices during the period from November 2018 to March 2019. 297 Hospital and community pharmacies from public and private sectors were contacted for carrying out this study survey and the collected data were analysed against WHO standards for core drug use indicators. Results The average number of drugs per encounter was 3.98 drugs. Hospital pharmacies had a higher (4.18±1.516) number of drugs prescribed than community pharmacies (3.87±1.331) with significance difference between mean of two types of pharmacies (P = 0.015). The percentage of antibiotic per prescription was (53.7%). Antibiotic prescribing was much higher (54.0%) in the hospital pharmacies compared to (48.6 %) in community pharmacies. The average percentage of injections per prescription at the facilities was found to be (57.6%). The percentage of prescription with written diagnosis was (26%.0) and the percentage of prescriptions with written dose was (78%.0). The average dispensing time was (1.75) minutes, The Percentage of drugs actually dispensed was (55.99%), the average adequacy of labelling of drugs was (30.4%). Overall prescribing and dispensing indicators were higher than WHO standard. Conclusion The degree of poly pharmacy was greater than of WHO criteria. The completeness and rationality of prescription was found suboptimal and components were missed.
Keywords: Prescribing practice; Dispensing practice; Patient care indicators; WHO indicators.